2022
DOI: 10.1098/rspb.2022.0474
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of an ancestral pheromone biosynthetic pathway contributes to diversification in Heliconius butterflies

Abstract: During courtship, male butterflies of many species produce androconial secretions containing male sex pheromones (MSPs) that communicate species identity and affect female choice. MSPs are thus likely candidates as reproductive barriers, yet their role in speciation remains poorly studied. Although Heliconius butterflies are a model system in speciation, their MSPs have not been investigated from a macroevolutionary perspective. We use GC/MS to characterize male androconial secretions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 85 publications
(142 reference statements)
3
15
0
Order By: Relevance
“…Visualisation of the results showed that individuals were mostly grouped by clade, with few deviations (Figure 29) and that most of the variation in CSG composition was explained by species identity (Figure 29), as found in previous studies [15,20,23] . Thus, species identity appears to be a strong predictor of CSG composition previously reported for the male androconial compounds [48] . Nevertheless, some overlap between species occurs.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Visualisation of the results showed that individuals were mostly grouped by clade, with few deviations (Figure 29) and that most of the variation in CSG composition was explained by species identity (Figure 29), as found in previous studies [15,20,23] . Thus, species identity appears to be a strong predictor of CSG composition previously reported for the male androconial compounds [48] . Nevertheless, some overlap between species occurs.…”
Section: Resultssupporting
confidence: 79%
“…Often certain compounds are found in several species, suggesting a common biosynthetic machinery within the heliconiines. Previous results suggest that most CSG compounds are indeed biosynthesised de novo [20,48,55] . The current analyses and previous work [9,15,20,23] indicate that some compounds or groups are particularly important, in addition to those with proven function ( 1 – 5 ).…”
Section: Compounds Of the Csgssupporting
confidence: 56%
See 1 more Smart Citation
“…24). 120 H. erato is an exception, lacking any fatty acid metabolites. The androconia contain small amounts of geranylgeranylacetone ( 119 ), 94 but the major component is terminally oxidized 119 conjugated to fatty acids, which is non-volatile.…”
Section: Heliconiinaementioning
confidence: 99%
“…The fatty acid metabolic pathway was recruited by more advanced genera to arrive at more complex blends, while basal lineages are dependent on plant metabolites such as 117–120 , or geranylgeranyl acetate ( 123 ) of H. erato and H. himera . 120 The fatty acid derived compounds include mostly compounds similar to type I moth pheromones compounds such as 116 and hexadecanal ( 132 ) of H. aoede , 1-hexadecanol ( 124 ), ( Z )-9-octadecen-1-ol ( 125 ) of H. xanthocles , ( Z )-11-eicosen-1-ol ( 126 ) of H. atthis , ( Z )-13-docoscen-1-ol ( 127 ) of Eueides tales , ( Z )-11-eicosenyl acetate ( 128 ) of E. aliphera , but also alkanes such as heneicosane, tricosane, and ( Z )-9-tricosene ( 129 ) of H. charithonia , as well as (3 Z ,6 Z ,9 Z )-3,6,9-henicosatriene ( 130 ) of H. demeter , a typical type II moth pheromone (Fig. 24).…”
Section: Heliconiinaementioning
confidence: 99%